Knowledge, awareness and attitude related to hypertension and garlic supplement in an urban population - Farida Islahudin; Nurul Aqidah Adnan; Ong, Wuey Chen; Fatin Najiha Rahman; Malina Jasamai (Penerbit Universiti Kebangsaan Malaysia, 2020)
Garlic has gained popularity worldwide as a non-pharmacological treatment for hypertension but its use in Malaysia is still moderate. This study was undertaken among Malaysian urban population to assess their knowledge, awareness and attitude towards garlic supplement. This study is a cross sectional study and was carried out from February to May 2015. A total of 202 respondents took part in the study with 45% (n=91) taking garlic supplement. The result demonstrated that there was a significant negative correlation with age and knowledge score (r=-0.15, p=0.03). Majority of the respondents were unaware (n=61/202, 69.8%) that garlic has blood pressure lowering properties. Most preferred conventional medicines (n=119/202, 58.9%) over garlic supplement (n=83/202, 41.1%). However, most of the respondents (n=176/202, 87.1%) were interested to know more about the use of garlic for hypertension. There is no significant correlation between knowledge, awareness and attitude of respondents towards garlic supplement.